\(\cfrac{4\sqrt{3}}{2−\sqrt{2}}−\cfrac{30}{4\sqrt{3}−\sqrt{18}}−\cfrac{\sqrt{18}}{\sqrt{3}−\sqrt{12}}\)
\(=\cfrac{4\sqrt3 (2+\sqrt2)}{(2-\sqrt2)(2+\sqrt2)} \)
\(-\cfrac{30(4\sqrt3+\sqrt{18})}{(4\sqrt3-\sqrt{18})(4\sqrt3+\sqrt{18})}\)
\(-\cfrac{\sqrt{18} (3+\sqrt{12})}{(3-\sqrt{12})(3+\sqrt{12})} \)
\(=\cfrac{4\sqrt3 (2+\sqrt2)}{4-2}-\cfrac{30(4\sqrt3+\sqrt{3\times3\times2})}{48-18}\)
\(-\cfrac{\sqrt{3\times3\times2}(3+\sqrt{2\times2\times3})}{9-12}\)
\(=\cfrac{4\sqrt3 (2+\sqrt2)}{2}-\cfrac{30(4\sqrt3+3\sqrt2)}{30}\)
\(-\cfrac{3\sqrt2 (3+2\sqrt3)}{-3}\)
\(=2\sqrt3 (2+\sqrt2)-(4\sqrt3+3\sqrt2)\)
\(+\sqrt2 (3+2\sqrt3)\)
\(=4\sqrt3+2\sqrt6-4\sqrt3-3\sqrt2+3\sqrt2+2\sqrt6\)
\(=4\sqrt6\) (Answer)